2020
DOI: 10.1002/anie.202000175
|View full text |Cite
|
Sign up to set email alerts
|

Cs2PtI6 Halide Perovskite is Stable to Air, Moisture, and Extreme pH: Application to Photoelectrochemical Solar Water Oxidation

Abstract: Halide perovskites show incredible photovoltaic power conversion efficiency coupled with several hundreds of hours of device stability. However, their stability is poor in aqueous electrolyte media. Reported here is a vacancy ordered halide perovskite, Cs2PtI6, which shows extraordinary stability under ambient conditions (1 year), in aqueous media of extreme acidic (pH 1), basic (pH 13), and under electrochemical reduction conditions. It was employed as an electrocatalyst and photoanode for hydrogen production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 43 publications
(49 reference statements)
6
49
1
Order By: Relevance
“…Figures 4c and S13b clearly show that 0.22 electrons are transferred from Pt to N, which is consistent with the fact that Cs 2 PtI 6 is a typical n-type material. 51 The resistance of the perovskite shows an ascending trend, which is consistent with test results.…”
supporting
confidence: 88%
“…Figures 4c and S13b clearly show that 0.22 electrons are transferred from Pt to N, which is consistent with the fact that Cs 2 PtI 6 is a typical n-type material. 51 The resistance of the perovskite shows an ascending trend, which is consistent with test results.…”
supporting
confidence: 88%
“…For example, the vacancy‐ordered halides of Sn IV , [11] Se IV , [12] Te IV , [13, 14] and Ti IV , [15] have shown to be promising photovoltaic materials. The analogous variants of heavier transition metals such as Pt IV , [16, 17] and Pd IV , [18] have also been reported. Separately, there has been significant interest in the single‐ion physics of vacancy‐ordered double perovskites and related systems of heavy transition metals.…”
Section: Figurementioning
confidence: 89%
“…30 Finally, Chen et al reported Cs 2 TiBr 6 PSCs with a stable efficiency of 3.3%, corroborating the promising potential of Tibased vacancy-ordered double halide perovskites in photovoltaic applications. 31 However, these studies mainly focused on a few select TM elements, such as Pt, 32 Ti, 33 and Pd., 34 Although double perovskites exhibit greater stability than HPSCs, they typically have wide band gaps of >1.5 eV, significantly lowering the photovoltaic efficiency. It is therefore necessary to develop a lead-free stable narrow bandgap perovskite material for photovoltaic applications.…”
Section: ■ Introductionmentioning
confidence: 99%